2017
DOI: 10.1016/j.dental.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

ADM guidance-ceramics: Fatigue principles and testing

Abstract: This ADM guidance document aims to summarize the aspects related to fatigue degradation of dental ceramics, reviewing the concepts of fatigue testing and furthermore aims to provide practical guidance to young scientists entering into fatigue related research. The description of fatigue strength is always accompanied by a clear understanding of the underlying fracture mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(59 citation statements)
references
References 77 publications
3
56
0
Order By: Relevance
“…Ideally, fatigue or aging should be tested by cyclic loading until fracture [31]. Very few previous studies have shown any effect of cyclic loading at sub-critical load prior to quasi-static loading.…”
Section: Aging Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, fatigue or aging should be tested by cyclic loading until fracture [31]. Very few previous studies have shown any effect of cyclic loading at sub-critical load prior to quasi-static loading.…”
Section: Aging Proceduresmentioning
confidence: 99%
“…Aging of zirconia crowns has been investigated by a large number of in vitro trials [20,22,[35][36][37][38]. However, there is no consensus regarding the method to mimic a clinically relevant aging [31]. High temperature, thermo-cycling and cyclic loading have all been used to provoke aging, either alone or in different combinations.…”
Section: Aging Proceduresmentioning
confidence: 99%
“…3,11 Many articles have been published in the past few years providing valuable input in understanding this topic and guiding new research. 1,10,12,13 Nevertheless, reviewing recent publications shows considerable variations in fatigue testing methodologies, which make the comparability of results a serious challenge. Fatigue testing studies vary in many aspects such as the number and frequency of cycles, abutment and antagonist materials, periodontal ligament (PDL) simulation, and sometimes thermocycling protocols.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Kelly et al [20] developed an in vitro test assembly that better simulates the failure mechanism and stress state observed in clinically retrieved failed prostheses (e.g. radial cracks starting from the cementation surface -tensile side) [21].…”
Section: Introductionmentioning
confidence: 99%